2017
DOI: 10.1038/srep43460
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the emergence of modern humans and the disappearance of Neanderthals: Insights from Kaldar Cave (Khorramabad Valley, Western Iran)

Abstract: Kaldar Cave is a key archaeological site that provides evidence of the Middle to Upper Palaeolithic transition in Iran. Excavations at the site in 2014–2015 led to the discovery of cultural remains generally associated with anatomically modern humans (AMHs) and evidence of a probable Neanderthal-made industry in the basal layers. Attempts have been made to establish a chronology for the site. These include four thermoluminescence (TL) dates for Layer 4, ranging from 23,100 ± 3300 to 29,400 ± 2300 BP, and three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 43 publications
1
35
1
1
Order By: Relevance
“…A number of sites in Central and Southern Zagros have yielded variably rich Mousterian lithic assemblages (e.g., Biglari, 2007;Otte et al, 2009;Scott and Marean, 2009;Bazgir et al, 2014Bazgir et al, , 2017Shidrang et al, 2016;Becerra-Valdivia et al, 2017;Heydari-Guran and Ghasidian, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A number of sites in Central and Southern Zagros have yielded variably rich Mousterian lithic assemblages (e.g., Biglari, 2007;Otte et al, 2009;Scott and Marean, 2009;Bazgir et al, 2014Bazgir et al, , 2017Shidrang et al, 2016;Becerra-Valdivia et al, 2017;Heydari-Guran and Ghasidian, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Sus scrofa dominates the Palearctic and Oriental regions and is also known from El Harhoura 2 Cave, Morocco (Michel et al, 2009). In the eastern Saharo-Arbian region, Delagnes et al (2012) reported nine suid teeth and tooth fragments from Western Yemen, and Sus remains were also reported from Jordan (Martin et al, 2010) and Iran (Trinkaus et al, 2008;Bazgir et al, 2017).…”
Section: Late Pleistocene Distribution 31 Suidaementioning
confidence: 99%
“…Both Ce. elaphus and Capreolus capreolus are known from eastern Saharo-Arbian in Iran (Trinkaus et al, 2008;Bazgir et al, 2017) and represent the only known cervids from this region during the Late Pleistocene.…”
Section: Cervidaementioning
confidence: 99%
“…However, so far, the Late Pleistocene human remains in Iran (Trinkaus and Biglari, 2006;Zanolli et al, 2019) are scarce. On the contrary, considerable lithic assemblages associated to the Middle Palaeolithic (Zagros Mousterian; Dibble, 1984) and Upper Palaeolithic (Zagros Aurignacian: Olszewski and Dibble, 1994;Baradostian: Solecki, 1958;Rostamian: Conard and Ghasidian, 2011 ) are known to be concentrated in the Zagros foothills (mainly in caves and rock shelters) (e.g., Biglari, 2001;Otte et al, 2007;Shidrang et al, 2016;Bazgir et al, 2017;Heydari-Guran and Ghasidian, 2017). Beyond the Zagros foothills, several open-air sites in stratigraphic context have recently been discovered in the northern and western edges of the Iranian Central plateau, as well as the central Alborz (e.g., see Berillon et al, 2007;Berillon and Asgari Khaneghah, 2016;Conard et al 2009;Heydari-Guran et al 2014;Vahdati Nasab and Hashemi 2016;Vahdati Nasab et al, 2013;2019).…”
Section: Mirak Open-air Site In a Prehistorical Contextmentioning
confidence: 99%